Abordaje conservador y mínimamente invasivo de la hipomineralización molar-incisivo (HMI) - Relato de casos clínicos - Restrepo, Manoel Restrepo; Fragelli, Camila Maria Bullio; Bussaneli, Diego Girotto; Souza, Juliana Feltrin De; Jeremias, Fabiano; Cordeiro, Rita de Cássia Loiola [UNESP]; Santos-pinto, Lourdes (My University, 2014)
Molar-Incisor Hypomineralization (MIH) is a qualitative developmental enamel defect that affects one to four permanent first molars, with or without involvement of permanent incisors. Enamel defects may produce many symptoms that have physical, social and psychological effects and influence day-to-day living or quality of life. The available treatment modalities for teeth with MIH are extensive, ranging from prevention, restoration, to extraction. Factors such as age, patient expectations, severity of the lesion and materials should be considered in the treatment of the patient with MIH. Restoration with composite resin is an alternative choice for posterior and anterior MIH defective teeth and its use has been show acceptable results. This article describes two clinical cases involving pediatric patients with MIH whose procedure of cavity preparation was based on the use of CVD ultrasound diamond tips and restored using composite resin obtaining favorable esthetics results after a 1 year follow-up.

La Hipomineralización Molar-Incisivo (HMI) es un defecto de esmalte de origen sistémico que afecta uno o varios molares permanentes, asociado en algunos casos a los incisivos permanentes. Defectos de esmalte, como la HMI pueden influenciar negativamente la calidad de vida, percepción estética y autoestima de niños y adolescentes. Las opciones de tratamiento para este tipo de alteración, incluye desde medidas preventivas y procedimientos restauradores hasta la extracción dental. Factores como la edad y expectativas del paciente, severidad de la alteración y materiales deben ser considerados en el plan de tratamiento del paciente con HMI. La utilización de resinas compuestas para la restauración de molares e incisivos ha mostrado buenos resultados relacionados a la durabilidad y estética. Este artículo presenta dos casos clínicos sobre el abordaje de la HMI en dientes anteriores, realizando preparos cavitários conservadores por medio de puntas ultrasónicas adaptadas a un sistema de ultrasonido y restauración con resina compuesta, obteniendo resultados estéticos favorables con un año de acompañamiento.
Minimally invasive treatment for esthetic management of molar-incisor hypomineralization (MIH): A case report
Keywords: Dental enamel; Composite dental Resin; Esthetics; Molar Incisor Hypomineralization; Esmalte dental; Terapia por ultrasonido; Estética